The Effect of Circuit Training Methods, Circuit Series and Learning Motivation on Students’ Volleyball Basic Skill - astuti, yuni (LPPM Undiksha, 2018)
This research was conducted to reveal the influence of circuit training methods, circuit series and learning motivation on basic volleyball technical skills of students of Bung Hatta University Health and Recreation Health and Education Study Program, Bung Hatta University. The purpose of this study is to analyze the differences of the influence of circuit training methods and circuit series and to see students' learning motivation towards their basic skills of volleyball. This research was conducted at Bung Hatta University volleyball court. This study was a quasi experiment with quantitative approach. The technique of data analysis was t-test. Based on the results of data analysis, it was found that: 1) there was a significant effect between the method of circuit training on volleyball basic technical skills with tcount = 16.90 and ttable = 2.20; 1) there was a significant influence between the circuit series method on the basic skills of volleyball with tcount = 9.62 and ttable = 2.20; 3) student learning motivation variables obtained the achievement level of 76.52%. This means that students have good learning motivation in following basic volleyball skills training, which is in the good category.